Synthesis of Benzylidene Analogs of Oleanolic Acid as Potential α-Glucosidase and α-Amylase Inhibitors - Ke, Jun-Jie; Lin, Jing; Zhang, Xin; Wu, Xiao-Zheng; Zheng, Ying-Ying; Hu, Chun-Mei; Kang, Yu; Zhang, Kun; Xiong, Zhuang; Ma, Zhi-Qiang (Frontiers in Chemistry, 2022)
A series of benzylidene analogues of oleanolic acid 4a~4s were synthesized and assessed for their α-glucosidase and α-amylase inhibitory activities. The results presented that all synthesized analogues exhibited excellent to moderate inhibitory effects on α-glucosidase and α-amylase. Analogue 4i showed the highest α-glucosidase inhibition (IC50: 0.40 μM), and analogue 4o presented strongest α-amylase inhibition (IC50: 9.59 μM). Inhibition kinetics results showed analogues 4i and 4o were reversible and mixed-type inhibitors against α-glucosidase and α-amylase, respectively. Simulation docking results demonstrated the interaction between analogues and two enzymes, respectively. Moreover, analogues 4i and 4o showed a high level of safety against 3T3-L1 and HepG2 cells.